2019
DOI: 10.33788/rcis.67.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Parenting Style and Anxiety in a Spanish Children Sample

Abstract: The aim of this study is to ascertain whether there are any diff erences in the parenting practices experienced by two groups of children with, respectively, low-risk and high-risk scores for anxiety. A second objective is to determine which parenting variables are linked with the presence or absence of this kind of internalizing problem. From a sample of 550 subjects, we selected 180 children between 3 and 12 years of age who met a set of specifi c criteria as having either high risk scores (90 children) or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…With regard to the first objective, the results showed that internalizing problems in children occur less frequently when both parents receive more support in parenting, show greater discipline, provide more autonomy to their children, and when the mother feels greater satisfaction with parenting. The results coincide with those obtained by Aguilar et al 7 Raya et al 9 Toro, 18 and Yap et al 19 which also showed that these were the parenting style factors most closely related to the frequency of some internalizing problems. Regarding autonomy, the results obtained coincided with those of Ezpeleta et al 14 in that the children who manifested more emotional problems after COVID-19 had perceived more overprotection by their parents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With regard to the first objective, the results showed that internalizing problems in children occur less frequently when both parents receive more support in parenting, show greater discipline, provide more autonomy to their children, and when the mother feels greater satisfaction with parenting. The results coincide with those obtained by Aguilar et al 7 Raya et al 9 Toro, 18 and Yap et al 19 which also showed that these were the parenting style factors most closely related to the frequency of some internalizing problems. Regarding autonomy, the results obtained coincided with those of Ezpeleta et al 14 in that the children who manifested more emotional problems after COVID-19 had perceived more overprotection by their parents.…”
Section: Discussionsupporting
confidence: 91%
“…Relatively several recent studies, such as Aguilar et al 7 have found that parenting styles focused on overprotection or excessive control by both parents have a greater impact on the development of anxiety during childhood and adolescence. With children between the ages of 3 and 12, it has been shown that parental behaviors focused on affection and communication not only affect acceptance and rejection but also increase the risk of depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation